EXTERNAL DEVELOPMENT FACTORS OF UNIVERSITY LECTURERS - Rutkiene, Ausra; Ančlauskaitė, Jolita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the context of the knowledge society the university teachers face increasing challenges. They are required a wide range of education as well as a constant desire for improvement fallowing up and applying innovations in their work. This article examines the teaching of a university lecturer in a non-formal or an informal way in order to find out what factors lead by representatives of this field trying to improve their competencies as the knowledge creator and disseminator. The survey was conducted by interviewing university lecturers during a semi-structured interview. The results of empirical research have shown that non-formal or informal learning for teachers is an integral part of their professional activity and they tend to pursue their personal interests in the most part in gaining knowledge or new experience to satisfy their curiosity, to satisfy students or to overcome certain challenges. In the professional environment, the impetus for learning is felt through the improvement of the quality of students and lectures, the desire to be equal partners in science to their colleagues and the perception that the teaching profession requires multidisciplinarity. Continuous learning has also been identified as a condition for pursuing a career or simply to maintain a job and meet the high academic requirements of the teaching profession.